A temporary corneal ectasia following airbag trauma - Marta, Ana (2021)
Purpose: To report a case of a temporary corneal ectasia induced by airbag trauma. Observations: A patient who suffered a road traffic accident with deployment of the frontal airbag and presented a corneal ectasia in both eyes after 3 months, without changes in visual acuity. After 9 months, he presented a significantly improvement, achieving his basal parameters in pentacam. Conclusions and importance: This is a rare case of corneal ectasia induced by airbag trauma that spontaneously reverted and it can emphasize the viscoelastic properties of the human cornea.